Pengaruh Audit Internal dan Kompetensi Account Officer terhadap Efektivitas Manajemen Risiko Pembiayaan di BRI Syariah Cabang Suniaraja - Gina Sahara; Widya Sari; Badriyatul Huda (Ma'soem University, 2021)
Based on observations, the background of this research is the increase in NPF at the BRI Syariah Bank Suniaraja Branch in the last five years. This study aims to determine how the influence of Internal Audit on the Effectiveness of Financing Risk Management at BRI Syariah Bank, to find out how the influence of Account Officer Competence on the Effectiveness of Financing Risk Management at BRI Syariah Bank, and to find out how the influence of Internal Audit and Account Officer Competence on the Effectiveness of Financing Risk Management. Simultaneously. The object of research in this report is to measure the internal audit and account officer at Bank BRI Syariah. The type of research is quantitative associative with primary data type and uses data collection techniques in the form of observation, literature study interviews and questionnaires. While the sampling technique is to use a saturated sample. The population is all account officers and internal audit employees, totaling 36 employees. The results showed that there was no direct influence between internal audit on the effectiveness of financing risk management with t test results tcount < ttabel (1,160 < 1,693), there was an influence between internal audit on account officer competence and t test results tcount < ttabel (3,076 > 1,693 There is an effect of account officer competence on the effectiveness of financing risk management with the results of the t test where tcount > ttabel (2,649 > 1,693 ), and simultaneously there is an influence between internal audit and account officer competence on the effectiveness of financing risk management with the results of the F test where Fcount > Ftabel (3.405 > 3.28).